Inter-Calibration and Limb Correction of FY-3D/E MWTS for Long-Term Gridded Microwave Brightness Temperature Dataset - Xia, Xinlu; Zeng, Mingjian; Luo, Xiaochun; Shi, Xiao; Jiang, Rongsheng; Yuan, Xinyi; Sang, Xiaozhuo; Tang, Fei; Xu, Xu (Remote sensing (Basel, Switzerland), 2025)
The Microwave Temperature Sounder-3 (MWTS-3) onboard the Chinese FengYun-3E (FY-3E) satellite is the third generation of Chinese microwave temperature sounder. Based on MWTS-2, the number of MWTS-3 channels has been increased from 13 to 17, which can observe the atmospheric temperature and water vapor profiles from the surface to the lower stratosphere. In this study, two generations of MWTSs onboard FY-3D/3E were inter-calibrated by the Double Difference (DD) method to eliminate bias. The results showed that the biases of tropospheric channels were stable (within 1 K) and the biases of stratospheric channels were relatively large (over 2 K). In addition, the weighting functions of all MWTS channels varied with fields of view (FOVs) due to different optical paths, causing the brightness temperature (TB) observations to display strong scan-dependent features, i.e., the limb effect. This work used a limb correction method to remove scan-dependent patterns so that the underlying weather signals could be uncovered. After inter-calibration and limb correction, this work converted the TB observations from MWTS-2/3 onto a global gridded dataset at 0.5° × 0.5° latitudinal and longitudinal resolutions using a method of nested interpolation. Based on this research, more long-term FengYun series satellite climate datasets can be established in the future.